7x-2y=6

Simple and best practice solution for 7x-2y=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-2y=6 equation:


Simplifying
7x + -2y = 6

Solving
7x + -2y = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2y' to each side of the equation.
7x + -2y + 2y = 6 + 2y

Combine like terms: -2y + 2y = 0
7x + 0 = 6 + 2y
7x = 6 + 2y

Divide each side by '7'.
x = 0.8571428571 + 0.2857142857y

Simplifying
x = 0.8571428571 + 0.2857142857y

See similar equations:

| x+(3x-5)+(x+2)=-48 | | 4x-x(x-4)=-9 | | (p+4)(2p+3)(p-1)=0 | | 2a^2-21a-65=0 | | 144x^3+68x^2-140x=0 | | 2085000000+5550000x=300000000 | | y/3+4=2y/5-6 | | x^2+11x-60=0 | | 3x-11=7x-35 | | 2=2-6b | | 6(2x-1)=3-(x+10) | | 9=12-3x | | x^2+25x+7= | | 4y^2+36y+81= | | 6x^2+7x=-12 | | x^6-6x^3+5=0 | | 3(1+x)=21+x | | 7-(4-9)= | | x-3=-1.5x+12 | | 3(2+x)=16+x | | -10-8x=-100+6x | | x-3=-1.5+12 | | 3x-28-5x=-(5x+13) | | 2s^2-13x-24=0 | | a^2-25a+16= | | k^2+5k+6= | | 5(x+4)=2+3 | | 4x-12=-24 | | 7x+21=-28 | | x^2+x^2=36 | | -110+6x=74 | | 4x^2+2x-17=0 |

Equations solver categories